Physiological quality of soybean seeds grown under different low altitude field environments and storage time - Oliveira, Kevein R; Sampao, F.R.; Siqueira, G.S.; Galvaeo, A.M.; Bennett, Sarita; Grataeo, P.L.; Barbosa, R.M. (Czech Academy of Agricultural Sciences, 2021)
The use of high-quality seeds is essential to maintain high rates of production and productivity. The physiological quality of seeds obtained in the field is directly correlated to storage conditions and storage time. This study aimed to evaluate the physiological quality of soybean seeds in relation to different field environments (seed lots) and storage time. Commercial lots of seeds of the soybean cultivar M8349 IPRO were stored for three and six months. Seed moisture content was determined before and after accelerated aging, along with seed germination percentage and vigour evaluations performed before and after each storage period. The experiment was carried out as a completely randomised factorial design (10 × 3): with ten seed lots and three storage periods. The data were analysed by ANOVA, and the means of four independent replicates for each parameter evaluated were compared using the Scott-Knott test at 5% probability (P ≤ 0.05). Our results revealed that the low altitude regions where the seed samples were collected are suitable for soybean seed production with high physiological quality. Seed storage for six months does not cause a significant reduction in subsequent soybean seed field performance.